An Evaluation of an LCD Display With 240 Hz Frame Rate for Visual Psychophysics Experiments. (October 2017) - Shi, Lin
Recently, a few LCD displays with 240 Hz frame rate have appeared on the market. I evaluated a LCD display with 240 Hz frame rate in terms of its temporal characteristics, progression between frames, and chromatic characteristics. The display showed (a) accurate frame durations at millisecond level, (b) gradual transition between adjacent frames, and (c) acceptable chromatic characteristics.